Reshaping the Future: The Tansformation of Museum Vocational Education Enabled by Artificial Intelligence - Rui Huang (Journal of Exploration of Vocational Education, 2025)
As artificial-intelligence technologies penetrate every facet of cultural-heritage preservation and dissemination, museums are redefining not only their public identity but also the very structure of the professional education that sustains them. At the vocational-education level, the urgent question is how to integrate AI tools organically with the knowledge domains of museum-related occupations. Focusing on the reshaping of museum vocational education, this paper proposes a future-oriented training framework anchored in four dimensions—creative education, technical practicum, competency cultivation, and systems design—and demonstrates its feasibility.